EFEKTIVITAS BENZOIL PEROKSIDA SEBAGAI INISIATOR PADA REAKSI ANTARA ASPAL DENGAN POLIMER YANG MEMANFAATKAN LIMBAH PLASTIK POLIPROPILENA DAN KARET BAN - Denny Akbar Tanjung; Dewi Nur Anggraeni (PROSIDING SEMINAR KIMIA, 2018)
Research on the effectiveness of benzoyl peroxide (BPO) as a reaction initiator between asphalt and polymer utilizing polypropylene plastic waste and tire rubber has been conducted, which aims to determine the effectiveness of BPO initiators in improving the mechanical properties (tensile strength) on asphalt mixtures, polypropylene, and rubber tire, and to identify group changes that occur after the use of BPO reviewed from the FTIR spectroscopy analysis. This research was conducted by mixing polypropylene which has been dissolved by xylene with tire rubber into glass and heated at 160 oC while stirring until homogeneous, which then added with asphalt, followed by the addition of BPO inisiator varied, which is then molded and flattened with a hot compressor machine at a temperature of 165 oC. The result was a tensile strength test which obtained maximum tensile strength on variation of 5 phr BPO addition for 60% asphalt mixture, 35% polypropylene, and 5% tire rubber which is 66,38 MPa. The results of characterization by FTIR spectroscopy show the presence of crosslinking between hydroxyl groups of asphalt with polypropylene through a radical reaction initiated by BPO. Keywords: Benzoyl Peroxide, Tire Rubber, Asphalt, Polypropylene, Tensile Strength, FTIR Spectoscopy.